PENYELESAIAN TINDAK PIDANA PENGHINAAN MELALUI MEDIASI PENAL PADA MASYARAKAT ADAT DI JORONG SALASA KENAGARIAN PADANG TAROK KECAMATAN BASO KABUPATEN AGAM - Ramadan, Rahmad; Firdaus, Emilda; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a state of law where every legal provision rests or is guided by Pancasila and the 1945 Constitution. Legislation should not conflict with higher regulations because they are required by the national. However, in societies other than the existence of a law that plays a national role there is also a customary law that was born and developed in the midst of a community called adat law. The purpose of this thesis discussion is: First, what is meant by the assistance of improvements to indigenous peoples in Jorong Salasa Kenagarian Padang Tarok, Baso District, Agam Regency. Second, what are the challenges in overcoming criminal acts on indigenous people in Jorong Salasa Kenagarian Padang Tarok, Baso District, Agam Regency.This type of research uses the method of sociological research because this study the author directly conducts research in a location or place that will gather complete information and explain about the problem to be discussed. This research was conducted in Jorong Salasa, Kenagarian, Padang Tarok, Baso District, Agam Regency, West Sumatra Province. Population samples and samples are study participants related to the problems discussed in this study. Data sources used are primary data, secondary data, tertiary data. Data collection techniques in this study were interviews and document studies.The Conclusions that can be drawn from this study Following are the conclusions that can be obtained from the results of the first research, Case Settlement through Penal Mediation on the follow-up of the Jorong Salasa Indigenous people of Padang Tarag Kenagarian Padang Tarag, Taro District, Baso District, Agam Regency has not been implemented well. The parties should have been able to approve the results of the decision of ninik mamak in completing the case through Penal Mediation for the prevention of the Indigenous people of Jorong Salasa Kenagarian Padang Tarag, Baso District, Agam Regency. as an alternative in resolving cases that occur in society. Second, While Constraints related to the process of settling court cases through mediation of criminal acts against indigenous people in Jorong Salasa Kenagarian Padang Tarok, Baso District include the absence of one party, uncooperative parties, requests for fines that need to be high, there is no need to convert people people who become law enforcement.Keywords: Settlement, Criminal Case, Penal Mediation, Customary Law, Insult.